(untitled) - Suy, Eric (Leuven, the Netherlands, 1996)
The book contains not only the relevant international traetises and convention concerning the fundamental questions on international law, but also Declarations on Principles adopted by the United Nations General Assembly and by the Conference on Security and Cooperation in Europe, Drafts by the International Law Commission on issues which are virtually accepted as reflecting the state of international law, and Drafts Convention in the field of international environmental law such as the Rio Convention on the Global Warming.
Keywords: Constitutional law